Becoming An Adaptive Teacher: Technology Literacy And Ethics In The Digital Era - Irmawati Thahir; Nurasia Natsir (Proceeding of the International Conference on Social Sciences and Humanities Innovation, 2025)
The digital era has fundamentally transformed the educational paradigm. This research examines the transformation of teachers' roles in addressing digital technology developments, particularly artificial intelligence (AI) and social media. The purpose of this study is to analyze the importance of technology literacy and digital ethics for teachers in creating adaptive and relevant learning environments. A literature review methodology is employed to identify key components required for teachers to transform into adaptive educators. The findings indicate that teachers need to develop five core competencies: understanding digital tools, critical information evaluation, interactive learning design, facilitating independent learners, and implementing technology ethics. This research contributes to developing a framework for adaptive teachers capable of utilizing technology as an opportunity rather than a threat in the educational process.